The Organization of Networking and Gender Inequality in the New Economy: Evidence from the Tech Industry. Issue 4 (November 2022) - Mickey, Ethel L.
In the new economy, with shrinking organizational supports and increased precarity for professional workers, networking has intensified as an entrepreneurial career management strategy. Networking is embedded in the logic of new work organizations, but less attention has been paid to its impact on gender inequality. Through fifty interviews with workers from one tech company and nine months of observations, I ask: (1) In the new economy, with intense networking demands, how does gender structure the networking strategies of workers? And (2) How does the organization of networking contribute to gender inequality? I find that individuals draw on masculinity and femininity as they network in ways that reproduce gender status hierarchies. The structure and culture of networking disproportionately limit the careers of women compared to men by shaping their (1) networking approaches; (2) attitudes about networking; and (3) resources gained from networking. Men network by strategically socializing, confidently building informal relationships with other men through masculine activities and leveraging these relationships for key resources. Women cannot similarly access informal relationships, and so they engage in strategic networking, attending formal networking events that are less effective in providing career resources. Women embodying an elite, white femininity locate personal support in the company-sponsored women's network. However, this group reinforces organizational boundaries by gender and race. This article advances sociological literature on inequality in the new economy, drawing on gender theory to demonstrate how in elite, male-dominated industries like technology, networking contributes to the maintenance of gender inequalities.